2022
DOI: 10.1038/s41598-022-16977-8
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of polyamide-12/cement nanocomposite and its testing for different dyes removal from aqueous solution: characterization, adsorption, and regeneration studies

Abstract: Polyamide-12/Portland cement nanocomposite was prepared by using the exfoliated adsorption method. The fabricated nanocomposite was applied first time to remove Congo red (CR), brilliant green (BG), methylene blue (MB), and methyl red (MR) from the synthetic wastewater. The polymer nanocomposite was characterized by Fourier transform infrared spectroscopy, scanning electron microscopy, energy-dispersive X-ray spectroscopy, elemental mapping, Brunauer–Emmett–Teller surface area analysis, and X-ray diffraction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…11 and Table 2 reveal that the kinetic data are best fitted and in excellent agreement with the pseudo–second–order kinetic model at all times along the whole adsorption process rather than the other studied models. This is in agreement with a previous study that used the cement nano-composite in the adsorption of both MB and CR dyes 48 . The regression coefficient (R 2 ) for the model is higher than 0.997, very near to the unit, and it is not only dependent on the initial concentration of the dye 49 .…”
Section: Resultssupporting
confidence: 93%
“…11 and Table 2 reveal that the kinetic data are best fitted and in excellent agreement with the pseudo–second–order kinetic model at all times along the whole adsorption process rather than the other studied models. This is in agreement with a previous study that used the cement nano-composite in the adsorption of both MB and CR dyes 48 . The regression coefficient (R 2 ) for the model is higher than 0.997, very near to the unit, and it is not only dependent on the initial concentration of the dye 49 .…”
Section: Resultssupporting
confidence: 93%
“…Instead, similar bandgap widening has been attributed to Burstein-Moss effect which is widely reported (for ZnO) in literature [25,63,64]. Nevertheless, based on the efficient absorption of pure and Mn-doped ZnO in the The Brunauer-Emmett-Teller (BET) method is ubiquitously utilized in nanotechnology and is envisaged to be an ideal experimental tool to estimate the specific surface area of the nanomaterials [65]. In the present study, a linear BET multipoint plot of 1/½WðP/P o Þ − 1 vs. P/P o has been obtained for both pure and Mn-doped ZnO photocatalysts.…”
Section: (A) (Inset)mentioning
confidence: 78%
“…The Brunauer–Emmett–Teller (BET) method is ubiquitously utilized in nanotechnology and is envisaged to be an ideal experimental tool to estimate the specific surface area of the nanomaterials [65]. In the present study, a linear BET multipoint plot of 1 / ][ W )( P / P o 1 vs. P / P o has been obtained for both pure and Mn-doped ZnO photocatalysts.…”
Section: Resultsmentioning
confidence: 99%
“…Ternes et al [ 16 ] reported that conventional methods, including oxidation, flocculation and coagulation, ion exchange, phytoremediation and sedimentation, are ineffective in eliminating the abovementioned substances from wastewater. On the other hand, the non-conventional method of adsorption is more effective and efficient [ [17] , [18] , [19] , [20] , [21] ]. The presence of benzene rings and functional groups on the structures of IBU and MB enhances the ability of carbonaceous material derived from agricultural waste to adsorb these substances from water [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%